PENGELOLAAN BIG DATA PERPUSTAKAAN DENGAN TEKNIK DATA MINING - Khusnul Khotimah; Husniyati (LPPM Universitas Muhammadiyah Kotabumi, 2020)
This article discusses the use of data mining in library big data processing using the association method. Data in the library becomes big data when it meets three criteria (volume, velocity, and variety). The association method is one of the methods of implementing data mining which aims to determine the relationship between data. In library big data, such as book lending data, the association method is used to determine the relationship between borrowers and borrowed collections. By knowing more quickly the library manager can determine the appropriate action based on the information generated. This is expected to help progress and good management of a library.